Introducing the International Confederation of Plastic Surgery Societies: ICOPLAST. Issue 3 (September 2017) - Rakhorst, Hinne A.; Badran, Hassan; Clarke, Howard M.; Cooter, Rodney; Evans, Gregory R. D.; Kirschbaum, Julio Daniel; Koh, Kyung Suk; Lazier, Carol; Murphy, Robert X.; Nakatsuka, Takashi; Piccolo, Nelson Sarto; Perks, Graeme
Abstract : Summary: This article describes the formation of the International Confederation of Plastic Surgery Societies (ICOPLAST) as a novel, transparent, dynamic, and proactive confederation of national plastic surgery societies. ICOPLAST aspires to provide a voice for the entire international community of plastic surgeons. ICOPLAST has been designed to benefit the patient, plastic surgery as a profession, and each individual plastic surgeon. Its principal objective is to enhance international communication, education, and advocacy processes to ultimately improve patient outcomes for plastic surgery patients globally. The new ICOPLAST's focus is to add true value for patients. ICOPLAST's evolution, philosophy, governance, and bylaws are explained and all societies worldwide are encouraged and cordially invited to join. An open and warm invitation is provided. Additional information is found atwww.ICOPLAST.org .